PENGARUH KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KETENANGAN KERJA PEGAWAI - Sumardi HR; Samsul Anwar (Universitas Wiralodra, 2022)
Human Resource Management is very important for an organization/company in managing, regulating and utilizing its employees so that they can function productively to achieve the goals of the organization. Work tranquility is a condition of a person's inner peace that is peaceful, free from problems, without any inner conflict, and without any pressure. This study aims to determine how much influence leadership has on employee peace of mind, influence of organizational culture on employee peace of mind, and the influence of leadership and organizational culture on employee calm at the Lelea sub-district office, Indramayu district. The method used is descriptive method using quantitative data types. The population in this study is leadership, organizational culture and work calmness of the employees of the Lelea District Office, Indramayu Regency. And the research sample amounted to 31 employees, and 10 employees were taken from Tukdana District, Indramayu Regency to test the validity and 1 leader to assess employees. The instrument used in this study was a questionnaire containing 30 statement questions. The results of the study indicate that the influence obtained from leadership on employee job satisfaction is in the medium category with a correlation coefficient value of 0.248, the influence of organizational culture on employee job satisfaction is in the medium category with a correlation coefficient value of 0.437, the influence of leadership and organizational culture on Employee Work Calm is classified as moderate category with a correlation coefficient value of 0.543. Hypothesis testing (f test) obtained the value of f Fcount is greater than Ftable (3.425> 3.34). So Ha is accepted and Ho is rejected, meaning that there is an influence of Leadership and Organizational Culture on Work Calm of Employees at the Lelea District Office, Indramayu Regency..